2015
DOI: 10.1590/bjpt-rbf.2014.0103
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy: a historical analysis of the transformation from an occupation to a profession in Brazil

Abstract: Background: Analyzing the historical and social path of an occupation using the sociology of professions and the perspective of scientific knowledge promotes an understanding of the origin of physical therapy in Brazil and of discussions of the profession in its contemporary context.Objective: The aim of this paper was to discuss the professionalization process of physical therapy in São Paulo. The authors tried to analyze bath therapy, massage therapy, and physical therapy as occupations involving distinct ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In terms of historical context, physical therapy has been influenced by economic, cultural, and educational aspects 3 of public and research policies that prioritize some fields of expertise over others. Among physical therapy’s specialties, occupational health and ergonomics is a novel example which is both increasing in clinical relevance and dissemination by professionals in a range of settings.…”
mentioning
confidence: 99%
“…In terms of historical context, physical therapy has been influenced by economic, cultural, and educational aspects 3 of public and research policies that prioritize some fields of expertise over others. Among physical therapy’s specialties, occupational health and ergonomics is a novel example which is both increasing in clinical relevance and dissemination by professionals in a range of settings.…”
mentioning
confidence: 99%
“…Previous studies showed that the professionalisation of physiotherapy in different countries had similar objectives including acquiring more autonomy and higher status, but it has occurred at considerably variable rates (Bergman and Marklund, 1989;Kenny and Adamson, 1992;Nicholls and Cheek, 2006;Oliveira and Nunes, 2015). Physiotherapists in western or developed countries are mostly autonomous, while the opposite is true to physiotherapists in some developing countries, such as India, Greece and Nigeria (Balogun, 2015).…”
Section: Resultsmentioning
confidence: 99%